Volga-Ural Cultural Group of the Post-Catacomb Period - Roman A. Mimokhod (Археология евразийских степей)
The article deals with a detailed description of the Volga-Ural cultural group. It occupied the steppes of the region of the same name in the final Middle Bronze Age, is part of the post-Catacomb cultural formations and is an integral part of the Lola culture area. The group is represented by burial mounds and ground burials. The main elements of its visual image are the adorative ritual and orientation to the southern sector. Of particular interest is the ritual group, which consists of burials made in a sitting posture or its imitation. In its development the group passed two stages within the period 2200-2000 CalBC. By its origin, the Volga-Ural cultural group was associated with the Lola culture, and its historical fate is closely connected with the formation of Sintashta antiquities.